2015
DOI: 10.1371/journal.pone.0139705
|View full text |Cite
|
Sign up to set email alerts
|

Rewriting the Central European Early Bronze Age Chronology: Evidence from Large-Scale Radiocarbon Dating

Abstract: The transition from the Neolithic to the Early Bronze Age in Central Europe has often been considered as a supra-regional uniform process, which led to the growing mastery of the new bronze technology. Since the 1920s, archaeologists have divided the Early Bronze Age into two chronological phases (Bronze A1 and A2), which were also seen as stages of technical progress. On the basis of the early radiocarbon dates from the cemetery of Singen, southern Germany, the beginning of the Early Bronze Age in Central Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 23 publications
2
48
0
5
Order By: Relevance
“…Stockhammer et al . 2015). Relieved of the burden of supplying dates, the material cultural assemblages can now be viewed more dynamically, allowing archaeologists to study the inner workings of these regional cultures and their patterns of interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Stockhammer et al . 2015). Relieved of the burden of supplying dates, the material cultural assemblages can now be viewed more dynamically, allowing archaeologists to study the inner workings of these regional cultures and their patterns of interaction.…”
Section: Introductionmentioning
confidence: 99%
“…cf. Stockhammer et al, 2015) was a time of major transformative cultural and social changes that led to cross-European networks of contact and exchange (Vandkilde, 2016). Intriguingly, recent studies on ancient human genomes suggested a major expansion of people from the Eurasian Steppe westwards into central Europe as well as eastwards into Central Asia and Southern Siberia starting around 4,800 BP (Allentoft et al, 2015;Haak et al, 2015).…”
mentioning
confidence: 99%
“…Such a linear and gradual view has been recently qualified by authors who consider that there was no sharp transition between the two EBA sub-periods, A1 and A2, but a complete overlap between the types of objects produced in these the two phases (Stockhammer et al, 2015). In other words, it is inaccurate to assume that the watershed of bronze production by UC tribes was 1800 B.C., with no or very few tin bronzes before that date and exclusively tin bronzes after that.…”
Section: The Development Of Bronze Production and The Use Of Tinmentioning
confidence: 94%